The Rationality behind Immigration Preferences - Hendrik P. van Dalen; Kène Henkens (Tinbergen Institute, 2004)
What drives stated preferences about the number of foreigners? Is it self-interest as stressed by the political economy of immigration? Does social interaction affect this preference or is the immigration preference completely in line with the preference for the aggregate population size? In this paper we distinguish each of these categories and show for the case of the Netherlands that each of these elements applies although the effect of population size preference and the self-interest are the most important elements. There is a clear divide across educational levels as the lower educated are more against immigration than the highly educated. Experience with foreigners arising from social contact matters in positively appreciating immigrants, especially if one meets (non-western) foreigners at work and school. Contact with foreigners while going out decreases the preference for immigrants. The ethnic composition of the neighbourhood in which one lives does not ex!ert a significant effect on the evaluation of the number of foreigners present. The biggest effect on immigration preferences is, however, the aggregate population size preference of respondents.
Keywords: F22; J15; J61; 330; Immigration; population; social interaction; public choice; Einwanderung; Migrationspolitik; Soziale Integration; Öffentliche Meinung; Niederlande